Direct intertectal inputs are an integral component of the bilateral sensorimotor circuit for behavior in Xenopus tadpoles - Gambrill, Abigail C. (J Neurophysiol, 2018)
The circuit controlling visually guided behavior in nonmammalian vertebrates, such as Xenopus tadpoles, includes retinal projections to the contralateral optic tectum, where visual information is processed, and tectal motor outputs projecting ipsilaterally to hindbrain and spinal cord. Tadpoles have an intertectal commissure whose function is unknown, but it might transfer information between the tectal lobes. Differences in visual experience between the two eyes have profound effects on the development and function of visual circuits in animals with binocular vision, but the effects on animals with fully crossed retinal projections are not clear. We tested the effect of monocular visual experience on the visuomotor circuit in Xenopus tadpoles. We show that cutting the intertectal commissure or providing visual experience to one eye (monocular visual experience) is sufficient to disrupt tectally mediated visual avoidance behavior. Monocular visual experience induces asymmetry in tectal circuit activity across the midline. Repeated exposure to monocular visual experience drives maturation of the stimulated retinotectal synapses, seen as increased AMPA-to-NMDA ratios, induces synaptic plasticity in intertectal synaptic connections, and induces bilaterally asymmetric changes in the tectal excitation-to-inhibition ratio (E/I). We show that unilateral expression of peptides that interfere with AMPA or GABA(A) receptor trafficking alters E/I in the transfected tectum and is sufficient to degrade visuomotor behavior. Our study demonstrates that monocular visual experience in animals with fully crossed visual systems produces asymmetric circuit function across the midline and degrades visuomotor behavior. The data further suggest that intertectal inputs are an integral component of a bilateral visuomotor circuit critical for behavior. NEW & NOTEWORTHY The developing optic tectum of Xenopus tadpoles represents a unique circuit in which laterally positioned eyes provide sensory input to a circuit that is transiently monocular, but which will be binocular in the animal’s adulthood. We challenge the idea that the two lobes of tadpole optic tectum function independently by testing the requirement of interhemispheric communication and demonstrate that unbalanced sensory input can induce structural and functional plasticity in the tectum sufficient to disrupt function.